Analysis of joint mobility patterns among preschool children - Lamari, Neuseli Marino; Chueire, Alceu Gomes; Cordeiro, José Antonio (São Paulo Medical Journal, 2005)
ONTEXT AND OBJECTIVE: Standardization of normal joint mobiliy criterb is complex, especiallyfor preschool children, for whom differentiation lrom hypermobility OH) is even more difficult. This study aimed to investigate joint mobility oi the lilth linger, wrist, elbow, knee and trunk among preschool eh ildren, estimate the incidence oi JH and evaluate the effect oi gender and age and the appl icability oi standard criteria for identilying JH among preschool children. DESIGN AND SETllNG: Cross-sectional descriptive and quantitative study, at São José do Rio Preto medical school. METHODS: 1, 120 healthy children (534 boys, 47.7%; 586 girls, 52 .3%; age range: 4-7 years) were evaluated using Beighton scores. Passive extension oi lilth linger I> 90º ), passive apposition oi thumb to forearm, aclive ex!ension oi elbow and knee I> 1 O º ) and anterior trunk llexion placing llat hand on ground were assessed. One point was scored for each positive result jmaximum: 9). Scores; 4 were considered to be JH. Student's t test and variance analysis were used for statistical analysis. RESULTS: JH was observed in 80% oi wrists, 53.3% oi lilth lingers, 36.6% oi elbows, 14% oi trunks and 12 .5% oi knees. Scores :?: 4 were lound for 64.6% oi the children. Females had h igher angular values. Lower scores were associated with greater age. CONCLUSIONS: JH is a common condition among preschool children and currently available methods are inadequate. New parameters and criteria should be developed for identilying JH among these children.